The external validation of the 2019 ACR/EULAR classification criteria for IgG4-related disease in a large cohort from China - Liu, Zheng; Nie, Yuxue; Peng, Yu; Lu, Hui; Zhang, Panpan; Li, Jieqiong; Sun, Ruijie; Li, Jingna; Sun, Boyuan; He, Xin; Zhou, Jiaxin; Fei, Yunyun; et al. (Seminars in arthritis and rheumatism, 2023)
To externally validate the performance of the 2019 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for IgG4-related disease (IgG4-RD) within a cohort from China and to compare the criteria with the 2020 revised comprehensive diagnostic (RCD) criteria for IgG4-RD. This study included 875 IgG4-RD and 302 non-IgG4-RD cases (213 mimickers and 89 patients with other diseases). Using expert clinical judgment as the gold standard for diagnosis of IgG4-RD, the performance (sensitivity, specificity, area under the curve (AUC) of the 2019 ACR/EULAR criteria for IgG4-RD was evaluated. We also compared it with the 2020 RCD criteria. The 2019 ACR/EULAR classification criteria had a sensitivity of 76.6% (95% CI: 73.8% to 79.4%) and a specificity of 98.0% (96.0%-99.4%), an AUC of 0.873 (0.857–0.889) in the overall cohort. Those false negative cases under the 2019 ACR/EULAR classification criteria had significantly lower levels of serum IgG4, and fewer had pathological information, with a higher frequency in the involvement of those uncommon organs compared with the true positive cases. The cases judged as negative by the 2019 ACR/EULAR classification criteria yet judged as “definite” by the 2020 RCD criteria had more involvement of uncommon organs. The 2019 ACR/EULAR classification criteria for IgG4-RD show outstanding specificity and good sensitivity in real-world clinical practice. The 2020 RCD criteria are helpful for the diagnosis of IgG4-RD in clinical scenarios where IgG4-RD presents as involving an isolated organ, especially the unusual sites.